Effects of gamma irradiation on collagen damage and remodeling. (March 2015) - Maslennikova, Anna; Kochueva, Marina; Ignatieva, Natalia; Vitkin, Alex; Zakharkina, Olga; Kamensky, Vladislav; Sergeeva, Ekaterina; Kiseleva, Elena; Bagratashvili, Victor
Abstract Purpose: To evaluate the dose-time dependences of structural changes occurring in collagen within 24 hours to three months after gamma-irradiation at doses from 2–40 Gy in vivo. Materials and methods: Rat's tail tendon was chosen as in vivo model, with its highly ordered collagen structure allowing the changes to be interpreted unambiguously. Macromolecular level (I) was investigated by differential scanning calorimetry (DSC); fibers and bundles level (II) by laser scanning microscopy (LSM), and bulk tissue microstructural level (III) by cross-polarization optical coherence tomography (CP-OCT). Results: For (I), the formation of molecular cross-links and breaks appeared to be a principal mechanism of collagen remodeling, with the cross-links number dependent on radiation dose. Changes on level (II) involved primary, secondary and tertiary bundles splitting in a day and a week after irradiation. Bulk collagen microstructure (III) demonstrated early widening of the interference fringes on CP-OCT images observed to occur in the tendon as result of this splitting. At all three levels, the observed collagen changes demonstrated complete remodeling within ∼ a month following irradiation. Conclusion: The time course and dose dependencies of the observed collagen changes at different levels of its hierarchy further contribute to elucidating the role of connective tissue in the radiotherapy process.